POLA KEBERTAHANAN SENI LONTAR PRASI DI DESA SIDEMEN, KECAMATAN SIDEMEN, KABUPATEN KARANGASEM - Ida Ayu Gde Wulandari; I Kadek Widiantana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This research is a qualitative research that examines how the existence of lontar prasi writers in Sidemen Village, Karangasem Regency. This research is very important because the existence of lontar prasi writers is very rare in Bali, and there is very little regeneration of prasi lontar writers. However, in Sidemen Village, where of the lontar prasi writer can still be found. This of course has a reason, and needs to be explored so that it can be imitated or developed in other places. Likewise, the opportunities and challenges of lontar prasi writers in the modern era like now are interesting things to study. In this regard, the matter that will be discussed is the pattern of survival of lontar prasi in Sidemen Village, Karangasem Regency. This qualitative research uses AGIL theory from Talcott Parson in solving problems and uses a qualitative approach, the result ofhe research data is able to maintain the integrity of the object. There are many various data related to research are understood as an integrated unit and the analysis is used qualitative descriptive methods. With the discovery of the pattern of survival of lontar prasi art, it is hoped that the art of lontar prasi can be developed in other places as a form of maintaining Balinese culture and traditions.